PERAN GURU BIOLOGI DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS XI SMA RAUDLATUSSALAM GLENMORE - Rohmah, Luluk Mufidatur Rohmah; Prasetiyo, Totok Hari Prasetiyo (Program Studi Pendidikan Biologi, 2024)
This study aims to look at the role of teachers in increasing students' learning motivation and the obstacles faced by teachers in increasing students' learning motivation using descriptive qualitative methods. From the results of the study, it was found that the teacher as a demonstrator must be able to demonstrate the material, as well as master the learning materials or materials to be taught, the teacher as a class manager, the teacher must be able to create a conducive and fun learning atmosphere, the teacher as a teacher mediator can maximize the use of media or teaching aids in teaching and learning activities. deliver the material, as well as the teacher as an evaluator who provides an evaluation at the end of the lesson, both in the form of tests, quizzes and responses to determine the level of student understanding and student learning outcomes, the obstacles faced by teachers in increasing student learning motivation are from the students themselves and from the environment. Islamic boarding schools that have many activities so that students become less enthusiastic in participating in learning at school. It can be concluded that the teacher's role has a relationship with the growth of learning motivation and student interest in learning itself in the teaching and learning process, the most dominant teachers in class XI IPA SMA Raudlarussalam are the teacher's role as a demonstrator, and teachers as class managers.